2021
DOI: 10.1002/joc.7238
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quantile Delta Mapping as a bias‐correction method in maximum rainfall dataset from downscaled models in São Paulo state (Brazil)

Abstract: An essential step for improving climate change models' performance is to evaluate their ability to represent the current climate conditions, especially extreme events. On such background, this study aims at evaluating the performance of the Quantile Delta Mapping (QDM) as a bias correction method for annual maximum daily precipitation series (bmax) generated from downscaled climate change models under tropical–subtropical conditions of Brazil. We selected the QDM due to its ability to correct bias in extreme q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The research results of correcting the earth system model of Beijing Normal University (BNU-ESM) by QDM and bias correction constructed analogs with quantile mapping reordering (BCCAQ) show that the QDM has a better performance compared to the BCCAQ method [ 35 ]. A study examined the performance of QDM in correcting the deviation of annual maximum daily precipitation, and the results showed that the QDM successfully adjusted the empirical cumulative distribution of climate change projections, removing the systematic error of raw data [ 36 ]. And the QDM also presented a suitable performance when applied to future projections.…”
Section: Methodsmentioning
confidence: 99%
“…The research results of correcting the earth system model of Beijing Normal University (BNU-ESM) by QDM and bias correction constructed analogs with quantile mapping reordering (BCCAQ) show that the QDM has a better performance compared to the BCCAQ method [ 35 ]. A study examined the performance of QDM in correcting the deviation of annual maximum daily precipitation, and the results showed that the QDM successfully adjusted the empirical cumulative distribution of climate change projections, removing the systematic error of raw data [ 36 ]. And the QDM also presented a suitable performance when applied to future projections.…”
Section: Methodsmentioning
confidence: 99%
“…For historical precipitation variable x , the projected truex̂m,ft can be written as (Eum et al ., 2020), truex̂m,ft=Fo,h1Fm,f()txm,ftmt, mt=xm,ftFm,h1Fm,f()txm,ft, where mt is relative ratio in a quantile between historical and future periods at time t , x m , f ( t ) and truex̂m,ft are raw uncorrected and bias‐corrected data from a climate model at time t within the projection period, F o , h is empirical cumulative density function (CDF) of observed values, F m , h and F m , f are the empirical CDFs of modelled data for historical and future periods, respectively. Brier score ( Bs ) is used as an indicator to reflect the effectiveness of QDM in precipitation projection (Miralha et al ., 2020; Xavier et al ., 2021), Bs=1Tfalse∑i=1T()Mtruêigoodbreak−Otruêi2, where M i and O i are the projected and observed values, respectively. T is the number o...…”
Section: Methodsmentioning
confidence: 99%
“…where 4 m t ð Þ is relative ratio in a quantile between historical and future periods at time t, x m,f (t) and b x m,f t ð Þ are raw uncorrected and bias-corrected data from a climate model at time t within the projection period, F o,h is empirical cumulative density function (CDF) of observed values, F m,h and F m,f are the empirical CDFs of modelled data for historical and future periods, respectively. Brier score (Bs) is used as an indicator to reflect the effectiveness of QDM in precipitation projection (Miralha et al, 2020;Xavier et al, 2021),…”
Section: Bias Correction Of Gcm Outputsmentioning
confidence: 99%
“…Thus, it becomes imperative to correct the RCM simulated meteorological variables before they could be used for impact studies (Mall et al., 2019; Seneviratne et al., 2012). Over the past decades, various bias correction methods are in use, these range from simple scaling approaches to sophisticated distribution mapping, quantile delta mapping and regional quantile delta mapping (RQDM) (Acharya et al., 2013; Chen et al., 2011, 2013; Fang et al., 2015; Gutjahr & Heinemann, 2013; Kim et al., 2021; Miralha et al., 2021; Piani et al., 2010; Sharma et al., 2007; A. Singh et al., 2017, 2021; Teutschbein & Seibert, 2012; Tiwari, Kar, Mohanty, Dey, Kumari, et al., 2016; Voropay et al., 2021; Xavier et al., 2021). Further, the bias in the daily rainfall values not only impact the monthly mean totals but also affect daily intensities, frequency, and other statistical properties at a different timescale that are used in agriculture as well as hydrological studies (Arnell et al., 2003; Choubin et al., 2019; Fowler et al., 2007).…”
Section: Introductionmentioning
confidence: 99%